Genome‐wide analysis of MIKC‐type MADS‐box genes in wheat: pervasive duplications, functional conservation and putative neofunctionalization. Issue 1 (1st October 2019) - Schilling, Susanne; Kennedy, Alice; Pan, Sirui; Jermiin, Lars S.; Melzer, Rainer
Summary: Wheat ( Triticum aestivum ) is one of the most important crops worldwide. Given a growing global population coupled with increasingly challenging cultivation conditions, facilitating wheat breeding by fine‐tuning important traits is of great importance. MADS‐box genes are prime candidates for this, as they are involved in virtually all aspects of plant development. Here, we present a detailed overview of phylogeny and expression of 201 wheat MIKC‐type MADS‐box genes. Homoeolog retention is significantly above the average genome‐wide retention rate for wheat genes, indicating that many MIKC‐type homoeologs are functionally important and not redundant. Gene expression is generally in agreement with the expected subfamily‐specific expression pattern, indicating broad conservation of function of MIKC‐type genes during wheat evolution. We also found extensive expansion of some MIKC‐type subfamilies, especially those potentially involved in adaptation to different environmental conditions like flowering time genes. Duplications are especially prominent in distal telomeric regions. A number of MIKC‐type genes show novel expression patterns and respond, for example, to biotic stress, pointing towards neofunctionalization. We speculate that conserved, duplicated and neofunctionalized MIKC‐type genes may have played an important role in the adaptation of wheat to a diversity of conditions, hence contributing to the importance of wheat as a global staple food.